Role of MicroRNAs and Retroelements in the Pathogenesis of Atherosclerosis - R. N. Mustafin; E. A. Galieva (SINAPS LLC, 2024)
Atherosclerosis is the leading cause of cardiovascular disease among adults. The incidence of atherosclerosis increases significantly with age, which indicates the possible influence of aging mechanisms on the development of the disease, including changes in epigenetic factors caused by pathological activation of transposable elements. Triggers of atherosclerosis are also viral infections, which promote the expression of retroelements that stimulate the interferon response with the development of chronic inflammation. Activated retroelements also alter the regulation of immune system genes and epigenetic factors, including the pathological production of microRNAs and long non-coding RNAs. A promising direction for atherosclerosis treatment is the epigenetic impact on the expression of specific genes involved in the pathogenesis of atherosclerosis using small interfering RNAs. In this regard, the drugs inclisiran and olpasiran have undergone clinical trials and have shown their effectiveness. Therefore, it is important to search for new molecular targets in this direction, which can serve as transposons, which are sources of non-coding RNAs. Changes in the activity of retroelements during aging have a global regulatory effect on the functioning of the entire genome, contributing to the development of age-associated pathology. An analysis of the scientific literature made it possible to identify 29 microRNAs derived from retroelements, changes in the expression of which have been identified both during aging and atherosclerosis. These microRNAs can be used as tools for prolonging life and treating cardiovascular pathology. The results obtained also indicate that retroelements pathologically activated during aging cause the development of atherosclerosis.